The Christian Applied Ethics Perspective on Divorce and Remarriage - Sitanggang, Laurent; Wijiati, Wahyu (JAKADARA: JURNAL EKONOMIKA, BISNIS, DAN HUMANIORA, 2025)
The issue of divorce and second marriage occupies a crucial position in the study of Christian applied ethics because it involves a tension between normative theological ideals and the empirical realities of human life. Within a theological framework, marriage is conceived as a covenantal union instituted by God, bearing sacred and ethical dimensions that demand fidelity, exclusivity, and permanence. From this standpoint, divorce is understood as an act that is normatively contrary to God’s intention as articulated in the biblical tradition. However, the complexities of human existence marked by sin, broken relationships, violence, and infidelity require an ethical approach that is not merely legalistic but also hermeneutical and pastoral. The findings of this study affirm that Christian applied ethics cannot be reduced to a literal application of biblical texts; rather, it must be approached as a holistic process of moral reasoning that integrates hermeneutical, theological, ecclesiological, and pastoral dimensions. Consequently, the church is called not only to uphold the sanctity of marriage but also to develop pastoral practices that are sensitive to the intricate realities of human struggle, so that decisions concerning divorce and second marriage may be situated within a framework of justice, mercy, and transformation that reflects the character of God.